2015
DOI: 10.14746/gl.2015.42.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Morphemic analysis increases vocabulary and improves comprehension

Abstract: The present study explored the effects of explicit and systematic teaching of morphemic analysis on vocabulary learning and comprehension. The reading class taught by the researcher was purposely taught the most common (30) prefixes and the most common (30) roots. Following fourteen 50-minute lessons, students were tested on their ability to recall the meanings of words used to teach the morphemic analysis skills, to derive meanings for new words that contained taught morphemic elements, and to comprehend text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…This is because knowing the prefixes helped in understanding the word meaning. The finding was consistent with the studies done by Talerico (2007), Baumann et al (2002), Jarad (2015), Khodadoust, Aliasin and Khosravi (2013), Kieffer and Box (2013), Nagy, Berninger and Abbot, (2006), and Zhang and Koda (2013). These studies found that learners were able to improve vocabulary acquisition through comprehending different parts of words.…”
Section: Category 1: Perception Of the Strategysupporting
confidence: 92%
See 3 more Smart Citations
“…This is because knowing the prefixes helped in understanding the word meaning. The finding was consistent with the studies done by Talerico (2007), Baumann et al (2002), Jarad (2015), Khodadoust, Aliasin and Khosravi (2013), Kieffer and Box (2013), Nagy, Berninger and Abbot, (2006), and Zhang and Koda (2013). These studies found that learners were able to improve vocabulary acquisition through comprehending different parts of words.…”
Section: Category 1: Perception Of the Strategysupporting
confidence: 92%
“…As can be seen in Item 3 in the questionnaire, learners did not seem to improve their confidence level in learning the language as the percentage was only 31.25% on the agree scale. This was in contrast with the study done by Jarad (2015) as the learners in his study improved in their confidence level. This was probably because the learners in the present study encountered some words that were difficult for them which was different from Jarad's study, where the learners were overwhelmed with the feeling that the words could be easily understood by dividing the words into the component parts when decoding their meanings.…”
Section: Category 1: Perception Of the Strategycontrasting
confidence: 76%
See 2 more Smart Citations
“…Morphological analysis instruction which is a strategy that enables EFL learners to acquire new words by analyzing the words' components to infer and understand inclusive word meanings can facilitate vocabulary learning for EFL learners (Brandes & McMaster, 2017). Jarad (2015) searched for the effects of morphemic analysis in increasing learners' vocabulary size and comprehension. The results indicated that the morphemic analysis strategy enhanced learners' vocabulary and comprehension.…”
Section: Morphemic Analysis and Vocabulary Instructionmentioning
confidence: 99%